2014
DOI: 10.1002/hipo.22334
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin phosphatase as a negative regulator of fear memory in hippocampus: Control on nuclear factor‐κB signaling in consolidation and reconsolidation

Abstract: Protein phosphatases are important regulators of neural plasticity and memory. Some studies support that the Ca(2+) /calmodulin-dependent phosphatase calcineurin (CaN) is, on the one hand, a negative regulator of memory formation and, on the other hand, a positive regulator of memory extinction and reversal learning. However, the signaling mechanisms by which CaN exerts its action in such processes are not well understood. Previous findings support that CaN negatively regulate the nuclear factor kappaB (NF-κB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 85 publications
3
18
0
Order By: Relevance
“…The results of the present study suggest that isoflurane activates NF-κB following mitochondrial dysfunction and CaN activation, and CaN is an upstream regulator of NF-κB activation. A complex interaction between CaN and NF-κB has been reported previously (32,33). CaN may dephosphorylate Bcl-10, which leads to IKKβ phosphorylation, IκBα degradation, RelA nuclear translocation and DNA binding in T helper cells (19).…”
Section: Discussionsupporting
confidence: 61%
“…The results of the present study suggest that isoflurane activates NF-κB following mitochondrial dysfunction and CaN activation, and CaN is an upstream regulator of NF-κB activation. A complex interaction between CaN and NF-κB has been reported previously (32,33). CaN may dephosphorylate Bcl-10, which leads to IKKβ phosphorylation, IκBα degradation, RelA nuclear translocation and DNA binding in T helper cells (19).…”
Section: Discussionsupporting
confidence: 61%
“…The hippocampus has been described to be involved in context associative memories (Smith and Bulkin, 2014) and the dynamics of the activation of NF-kappa B during memory consolidation in this and other paradigms has been widely reported (Freudenthal et al, 2005; de la Fuente et al, 2014, 2015; Salles et al, 2015; Zalcman et al, 2015). Specifically, the transcription factor NF-kappa B has been described to be necessary for memory consolidation in several species such as crabs and mice (Freudenthal and Romano, 2000; Freudenthal et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…However, SASP exerts many effects in addition to its ability to interfere with xCT function, so it cannot be considered a specific xCT inhibitor (39). Although recent preclinical models demonstrated that SASP impairs cancer growth and metastatic spread via xCT inhibition (15,17,40), its use in cancer patients is hampered by its low specificity, short bio-availability, and numerous side effects (41).…”
Section: Discussionmentioning
confidence: 99%